The Long Shadows of Gwangju: Transitional Criminal Justice in South Korea. (10th September 2022) - Vormbaum, Moritz
ABSTRACT ∞ : On 23 November 2021, the former South Korean president, Chun Doo-hwan, died at his home in Seoul less than a month after his successor Roh Tae-woo. Both men were leading figures during a dark period of the country's military dictatorships. The most egregious example of their authoritarian rule was the killing of hundreds of students and other persons who were protesting against the martial law government in Gwangju in 1980. On the occasion of the deaths of the two former presidents, this article offers an analysis of the events in Gwangju in the context of South Korea's contemporary history, before examining the criminal justice responses in the 1990s and more recently. In doing so, it presents and analyses the changing role of criminal law in extended periods of transitional justice.